CHRONIC PERIODONTITIS IN PATIENTS WITH CHRONIC DUODENAL ULCER - Kharchenko А.V.; Yelinska, A.M.; Shepitko, V.I.; Stetsuk, E.V. (World of Medicine and Biology, 2022)
The purpose of the study was to access the pathogenetic mechanism of the development of a combination of duodenal ulcers and chronic periodontitis. In 90 % of these patients, chronic gastritis was associated with Helicobacter pylori. In the mucous membranes of the gingival papillae and the mucous membrane of the stomach, one can notice similar inflammatory processes and processes that distinguish them. Such differences were found in the development of dystrophic processes, disturbance of regenerative and development of dysregenerative processes in the form of dysplasia of various degrees of expression in the gastric mucosa compared to the mucous membrane of the gingival papillae. There was a difference in the proliferative activity of these two mucous membranes. Frequency D of varying degrees was unidirectional and depended on the severity of gastritis and had a particular connection with the development of periodontitis in this group of patients. Thus, chronic atrophic gastritis in patients with chronic duodenal ulcers associated with Helicobacter pylori is a common disease. The degree of gastritis had a special relationship with the development and severity of periodontitis in this group of patients.